THE IMPACT OF SPECIALIZED EXERCISES ACCORDING TO THE LANDA MODEL IN LEARNING THE SKILL OF SERVING FROM THE BOTTOM IN VOLLEYBALL FOR STUDENTS - Adil, Daneez Samer; Ahmed, M.Manal Mohammed; Jamal, Mohammed Adil (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The researchers also attributed this to the educational units created by him, which had a significant impact on demonstrating the differences in his units' diversity, this information had a direct effect on increasing the students' desire and excitement while learning and developing skills without any form of boredom, this information had a positive effect on the teaching profession in regards to serving from below in the sport of volleyball.The researchers believe that Landa's educational philosophy is derived from the concept of continued interaction between the student and the teacher during the lesson. This interaction increases the students' capacity to participate in the conversation, which in turn increases their confidence.Through the results that were exhibited, the scientists concluded that follows: The two experimental groups (Landa's) that employed the Landa model had a positive effect on motor coordination and the learning of the serve from below in volleyball, however, the effect was different for each. The variety of educational endeavors participated in the students' acquisition of pertinent information. In view of the conclusions of the current study, the researchers make the following recommendations: Introduce specialized exercises based on the Landa model for students of the Faculty of Physical Education and Sports Sciences at the University of Kirkuk to improve some down-serve techniques in volleyball, as they play an effective role in improving the variables studied. Pay attention to the application of new models, including methods based on behavioral theories, which can help improve students' level and improve the educational process.